The Analysis of Traffic Delay and Queue due to the Shunting Activities of Pertamina Trains of Tegal City - Muhamad Yunus; Isradias Mirajhusnita; Rachmat Mudiyono; Hermin Poedjiastoeti (Universitas Islam Sultan Agung, 2020)
A crossing is a meeting point between roads and railways, where this often causes delays and traffic queues, as happened at the crossing on Jl. Abimanyu, Tegal City. This study aimed to analyze the volume, delay and queue length of traffic on each road which occured due to the closing of the railroad crossing. Apart from that, this research was also intended to provide reasonable alternative input for both the management of Pertamina and the road users. This research used the analysis method of v/c ratio, queue and delay with reference to the Manual for Indonesian Road Capacity. Results of the analysis show, the highest queue occurred on the Abimanyu road, which was of 70.5 pcu with the delay of 581.5 seconds/pcu. On the segment of Jl. Menteri Supeno I, the traffic queue was reported to have reached 47.8 pcu with the delay time of 441 seconds/pcu; on the segment of Jl. Semeru, the queue was reported to reach 17 pcu with the delay of 395.6 seconds/pcu, and the last one was the queue at the segment of Jl. Menteri Supeno II which was of 10.8 pcu, with the delay time of 368.5 seconds/pcu. Ones of the keys to overcome problems of traffic queues and delay were by dividing the shunting time into 2 phases according to the results of alternative analysis II where the traffic queue became smaller of 35.3 pcu with the delay time of 290 seconds/pcu and by changing the shunting schedule at off peak time.